Estudio de osmolalidad de una bebida a base de jícama (Pachyrhizus erosus) - Tamayo Nieves, Joyce Naomy (2022)
In the present research project, it was carried out with the purpose of obtaining a study of the osmolality of a drink based on jicama (Pachyrhizus erosus)”, for their respective formulations, an experimental design of A*B*C random complete blocks was carried out with 2 repetitions where the study factors were jicama-water ratio and jicama, types of sodium acid salts, magnesium citrate and citric acid; salt concentration 0.2g, 0.5g giving a total of 12 treatments. The response variables were evaluated using the InfoStat statistical program, giving T7 (a2b1c1) as the best treatment. It was the most acceptable in terms of osmolality, since it was chosen for its attributes in the organoleptic analysis as well; which corresponds to the jicama-based drink with the formulation of Jícama 100, Sodium Acid, 0.2g, for this reason it is prolonged that T7 corresponds to a hypertonic drink due to its osmolality value, which is 394mOsm/L. According to the physicochemical, microbiological and nutritional value analyzes of the best treatment T7 (a2b1c1). In the analysis carried out, the following results were obtained: a percentage of 0.55% ash, 0.23% protein, 9.42% total solids, 8.64% total carbohydrates, 477.97 mg/100g of sodium, these percentages are established within the established range of the INEN 783 standards. In the microbiological analysis of the best treatment, ˂10 molds, ˂10 total coliforms are ˂10 CFU/g, these do not indicate that it is within the parameters established according to the rule. It has a nutritional value of 21% sodium, 7% carbohydrates, 0% dietary fiber and 0% protein which is evaluated in a 2000 cal diet. This hypertonic drink has great sources of energy and necessary electrolytes that the body needs to rehydrate.